En'light'ening journey - Othman, Siti Sarah; Lim, Siang Hui; Faudzi, Hanis; Zeiss Malaysia (Universiti Putra Malaysia Press, 2017)
The saying ‘seeing is believing’ describes the curious nature of man to see things far smaller than can be perceived with the naked eye. It has been known for over 2000 years that glass bends light. Since then, many innovations have been made to manipulate light bending through different shapes of clear glass. These innovations paved the way for the development of the optical lens.